Integrasi Hukum Islam dalam Upacara Adat Batagak Panghulu di Minangkabau - Widia, Siska Mona; Miswardi, Miswardi; Nahdaturrahmi, Nahdaturrahmi; Wahyuni, Sri (Universitas Cokroaminoto Yogyakarta, 2025)
Minang society is known for its strong customs and religion, with philosophy of adat basandi syara', syara' basandi kitabullah, syara' mangato adaik mamakai. This research discusses the integration of Islamic values into the batagak panghulu traditional ceremony with empirical methods and qualitative data analysis based on field research. The results showed that Islam came to enlighten the creed of the people, Islam straightens, gives value, meaning and strengthening to the culture that already lives in Minangkabau society including in batagak panghulu ceremony. In Sutijo village, the selection of datuak and panungkek candidates is based on the prospective leader's understanding of Islamic religious. In the series of events of the batagak penghulu, the bundo kanduang must wear a tikuluak (head covering), and there are prohibitions on the datuak and panungkek who are not allowed to manyengsengkan langan baju jo sarawa, the determination of aurat, and the values ​​of togetherness so that this batagak panghulu ceremony has been in line with Islamic law.